An economic analysis of preimplantation genetic testing for aneuploidy by polar body biopsy in advanced maternal age. (4th February 2020) - Neumann, K; Sermon, K; Bossuyt, P; Goossens, V; Geraedts, J; Traeger‐Synodinos, J; Parriego, M; Schmutzler, A; van der Ven, K; Rudolph‐Rothfeld, W; Vonthein, R; Griesinger, G
Abstract : Objective: What are the cost per live birth and the incremental cost of preventing a miscarriage with preimplantation genetic testing for aneuploidy (PGT‐A) by polar body biopsy and array‐based comprehensive genome hybridisation (aCGH) versus regular IVF/ICSI without PGT‐A for infertility treatment in women 36–40 years of age? Design: Decision tree model. Population: A randomised clinical trial on PGT‐A (ESTEEM study). Methods: Two treatment strategies were compared: one cycle of IVF/ICSI with or without PGT‐A. Costs and effects were analysed with this model for four different cost scenarios: high‐, higher medium, lower medium and low‐cost. Base case, sensitivity, threshold, and probabilistic sensitivity analyses were used to examine the cost‐effectiveness implications of PGT‐A. Results: PGT‐A increased the cost per live birth by approximately 15% in the high‐cost scenario to approximately 285% in the low‐cost scenario. Threshold analysis revealed that PGT‐A would need to be associated with an absolute increase in pregnancy rate by 6% to >39% or, alternatively, would need to be US2, 969 (high‐cost scenario) to US4, 888 (low‐cost scenario) cheaper. The incremental cost to prevent one miscarriage by PGT‐A using the base case assumptions was calculated to be US34, 427 (high‐cost scenario) to US51, 146 (low‐cost scenario). A probabilistic sensitivity analysis showed cost‐effectiveness for PGT‐A from 1.9% (high‐cost scenario) to 0.0% (low‐cost scenario) of calculated samples. Conclusions: While avoiding unnecessary embryo transfers and miscarriages are important goals, patients and doctors need to be aware of the high‐cost implications of applying PGT‐A using aCGH on polar bodies. Tweetable abstract: PGT‐A by polar body biopsy and comprehensive genome hybridisation increases cost per live birth and requires high financial spending per miscarriage averted. Tweetable abstract: PGT‐A by polar body biopsy and comprehensive genome hybridisation increases cost per live birth and requires high financial spending per miscarriage averted.